A Network Analysis of the Stock Market in Malaysia, Singapore and Indonesia - Nur Iqmal Ibrahim, Siti; Aida Muhammad, Siti; Hafizah Abdullah, Mimi (International Journal of Engineering and Technology, 2018)
In this study, we investigate the stock market network among the stocks traded in Malaysia, Singapore and Indonesia using the minimal spanning tree approach. Based on the market capitalization, the monthly adjusted closing prices from 2016 until 2017 of 10 companies for each stock market are chosen to construct the network, and the most influential stocks between Malaysia, Singapore and Indonesia stock markets are identified. Findings of this study show that 3 out of 30 companies are identified as the most influential in the Malaysia, Singapore and Indonesia stock market.Â